Electrodiagnosis in New Frontiers of Clinical Research - Turker, Hande (IntechOpen, 2013)
Utilization of electrodiagnosis; namely electromyography (EMG), nerve conduction studies, late responses, repetitive nerve stimulation techniques, quantitative EMG and evoked potentials, has long been discussed in many text books as basic principles. However the usage of electroneuromyography is rather new in some aspects when compared with tasks of daily practise. This book, we believe, will cover and enlighten those aspects where electrodiagnosis has begun to play important roles nowadays.